2012
DOI: 10.1089/met.2011.0044
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Inflammatory Markers (High-Sensitivity C-Reactive Protein, Nuclear Factor-κB, and Adiponectin) in Indian Patients with Type 2 Diabetes Mellitus with and without Macrovascular Complications

Abstract: Indian subjects with T2DM with or without MVD had higher hsCRP and lower adiponectin values as compared to healthy controls, whereas hsCRP was significantly higher in those with MVD, suggesting that our patients with T2DM were in a proinflammatory state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Such proinflammatory state could be an independent determinant of atherosclerosis in this population. Further, this study has shown that persons with DM had significantly higher cholesterol and TG levels than non-DM counterparts [30].…”
Section: Discussionmentioning
confidence: 54%
“…Such proinflammatory state could be an independent determinant of atherosclerosis in this population. Further, this study has shown that persons with DM had significantly higher cholesterol and TG levels than non-DM counterparts [30].…”
Section: Discussionmentioning
confidence: 54%
“…Definition of diabetic foot infections (Table 8) indicate infectious diabetic foot as a "clinical syndrome characterized by the presence of local signs of inflammation such as redness, warmth, induration, pain or tenderness and purulence, sometimes in the context of a framework of sepsis, that occurs in a site below the malleoli in a person with diabetes" [61] . Infections on diabetic foot can represent a common and dangerous complication of diabetes owing to the fact that they can involve deeper soft and bone tissuse (cellulitis and osteomyelitis) thus significantly increasing the risk of amputation.…”
Section: Infections In Patients With Dfsmentioning
confidence: 99%
“…The pathways between negative and positive emotions and health outcomes interact through behavioral and/or biological mediators, both of which have relevance for DM, an illness characterized by underlying inflammatory changes [32,33] . Negative emotions can intensify a variety of health threats.…”
Section: Health Effects Of Emotions?mentioning
confidence: 99%